Meningkatkan Hasil Belajar Kognitif dan Kerjasama Peserta Didik melalui Lesson Study Berbasis Model Discovery Learning - Sudirman, Sudirman; Yusnaeni, Yusnaeni; Agustina, Indra Veny; Tanggal, Maria Y.Y.; Balu Lowa, Fransiskus X. (Jurnal Beta Kimia, 2023)
This research was carried out with the aim of knowing the increase in learning outcomes and cooperation of students in class XI MIPA 1 SMA Negeri 4 Kupang through Lesson Study based on the Discovery Learning Model. Implementation of the discovery learning learning model through Lesson Study in the LPTK Lecturer Partnership Program activities with teachers in schools in 2022. The research method used is Classroom Action Research combined with Lesson Study which consists of 2 cycles. Each cycle consists of activities: (1) Planning (Plan), (2) Implementation and Observation (Do), and (3) Reflection (See). The results of the research that has been done show that the application of lesson study based on the discovery learning model can improve cognitive learning outcomes and the collaborative abilities of students in class XI MIPA 2 SMA Negeri 4 Kupang NTT. The results of this study showed an increase in students' classical learning mastery from pre-cycle to cycle I reaching 33.33% and cycle II reaching 50.00%. While the ability to cooperate also increased, amounting to 55.56% in cycle I and increased by 83.33% in cycle II.